The Formation of Ecological Conscience as A Human and Pedagogical Problem - Cojocari-Luchian , Snejana (Journal of Danubian Studies and Research, 2023)
The world origin is organic bind to human origin. Nowadays the most advanced level of relation with nature is given by unitary and oneself nature understanding as basis element of these, the phenomenon defined by the term ecological conscience. But these isn’t proper than a little number of people. The relation human-nature has made up from the ancient times, which has been modifying always during the life, the man becoming final element of world and nature. The first people had been leaved in a perfect harmony with nature, being in the same time organic and integral part of these. The relation has modified during the history, from modification of ecological conscience the man has gone through the way of his consciousness as a nature object to his education as a muster of these, he succeeding to use it as a thing of material property, pretending to dominate it absolutely. The relation human-nature has unbalanced, its recovery being possible with changing of mentality by “isn’t mine, don’t care”, from ecological conscience formality, as a condition sine qua non of modern world. In this case, ecological education, it regains the main role, as the educational practice’s domain and science of education; it should integrate the all appeared factors and condition of ecological conscience.